How Strange the Change from Major to Minor - Peter Goodrich (Law Text Culture, 2017)
The lines from a Noel Coward song provide the appropriately melancholic and suitably ambiguous title to an excavation of the ontology of the minor. Associated theologically with the abrogation of all law, the minor is the child, play, the modal chord that challenges, subverts and displaces the certainty of the major key and black letter law. A minor jurisprudence is argued here to be a lifestyle that challenges the extant legal form of office, the establishment as doctrine, the stasis and complacency of the institution.